Decarbonisation of Road Transportation in India—A Round-Robin Review on Low-Carbon Strategies and Financial Policies - Shohel Amin (Future Transportation)
India is committed to becoming a net-zero emitter by 2070 to fight climate change; however, road transportation causes a major challenge for decarbonising transport in India. This paper investigates the low-carbon strategy and implementation of fiscal and financial policies in India. The research delves into the innovative strategies to address unique regional hurdles and transportation demands. These strategies include customised policies to incentivise EVs, creating charging infrastructure networks, the integration of renewable energy sources in public transport systems, and the formulation of specific regulations to curb emissions from high-traffic areas. Findings from the review of low-carbon strategies and financial policies in road transportation advocate for penalising high-emitters, subsidising clean technology, and reorienting government expenditure towards sustainable infrastructure for combating climate change and adhering to India’s commitment announced at COP26. This paper suggests the efficacy and replicability of these new strategies, thus, providing valuable insights to policymakers and stakeholders for creating a more sustainable and efficient road transportation network in India.